2012
DOI: 10.5114/aoms.2012.28558
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study on risk factors of breast cancer in China

Abstract: IntroductionTo screen the risk factors associated with breast cancer among Chinese women in order to evaluate the individual risk of developing breast cancer among women in China.Material and methodsA case-control study on 416 breast cancer patients and 1156 matched controls was conducted in 14 hospitals in 8 provinces of China in 2008. Controls were age- and region-matched to the cases. Clinicians conducted in-person interviews with the subjects to collect information on demographics and suspected risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 51 publications
3
32
1
Order By: Relevance
“…For example, obesity during pre-teen years (ages 5-10) is inversely related to breast cancer risk (Baer et al, 2010). On the other hand, obesity after menopause is positively related to breast cancer incidence (Bates and Carmichael, 2004;Lahmann et al, 2004;Cheraghi et al, 2012;Phipps et al, 2012;Xu et al, 2012). Although this is fairly well established, the relationship between premenopausal obesity and breast cancer risk remains less clear.…”
Section: Obesitymentioning
confidence: 91%
“…For example, obesity during pre-teen years (ages 5-10) is inversely related to breast cancer risk (Baer et al, 2010). On the other hand, obesity after menopause is positively related to breast cancer incidence (Bates and Carmichael, 2004;Lahmann et al, 2004;Cheraghi et al, 2012;Phipps et al, 2012;Xu et al, 2012). Although this is fairly well established, the relationship between premenopausal obesity and breast cancer risk remains less clear.…”
Section: Obesitymentioning
confidence: 91%
“…After reviewing the full text of these studies in detail, a total of 39 articles, involving 100,452 participants from 14 provinces, municipalities and regions, were included in the final review (Appendix 1). Among these included studies, we identified 6 cohort studies (Li et al, 2005;Shannon et al, 2005;Wang et al, 2006;Dai et al, 2010;Pronk et al, 2011;Shrubsole et al, 2011;) and 33 case-control studies (Lu et al, 1992;Xu et al, 1997;Zhao et al, 1999;Tao et al, 2002;Zou et al, 2002;Zhang et al, 2003;Chow et al, 2005;Lee et al, 2005;Chou et al, 2006;Huang et al, 2006;Li et al, 2006;Jin, 2007;Ma, 2007;Zhang et al, 2007;Kallianpur et al, 2008;Ren, 2008;Wang et al, 2008;Shrubsole et al, 2009;Wang et al, 2009;Zhang et al, 2009;Qian et al, 2010;Shi et al, 2010;Bao et al, 2011;Dai et al, 2011;Leu et al, 2011;Zhang et al, 2011;Hou et al, 2012;Xu et al, 2012;Yu et al, 2012;Wang et al, 2013). According to the NOS items, 11 studies were evaluated as high quality, 25 studies as modest quality, and 3 studies as low quality, respectively.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…During last decades major advances have been made in screening for risk factors associated with breast cancer in high-prevalence areas [2]. Knowledge regarding clinical symptoms of breast cancer and the possibilities of screening tests among healthy population is higher comparing to the other malignancies and wide acceptance among women for breast cancer screening results in increased detection rate of early breast cancer [3].…”
mentioning
confidence: 99%